2021
DOI: 10.3389/fimmu.2021.800188
|View full text |Cite|
|
Sign up to set email alerts
|

Dual Host and Pathogen RNA-Seq Analysis Unravels Chicken Genes Potentially Involved in Resistance to Highly Pathogenic Avian Influenza Virus Infection

Abstract: Highly pathogenic avian influenza viruses (HPAIVs) cause severe systemic disease and high mortality rates in chickens, leading to a huge economic impact in the poultry sector. However, some chickens are resistant to the disease. This study aimed at evaluating the mechanisms behind HPAIV disease resistance. Chickens of different breeds were challenged with H7N1 HPAIV or clade 2.3.4.4b H5N8 HPAIV, euthanized at 3 days post-inoculation (dpi), and classified as resistant or susceptible depending on the following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…A systemic review and meta-analysis of the virus shedding of avian influenza viruses [ 8 ] considered different explanatory variables for the viral shedding of AIVs in poultry species such as pathotype (HPAI/LPAI), shedding route, virus origin, inoculation route, age and chicken categories; it is reported that low viral shedding in chicken can be due to the avian host from which the virus originated. Moreover, some avian genes involved in resistance to clade 2.3.4.4b H5N8 HPAIV in commercial broilers (Ross 308 Broiler) and six local Spanish chicken breeds have recently been experimentally investigated [ 12 ] and PLAU, VCAM, TNFRSF1-1A and PGF gene expression, which are mainly involved in inflammation response, resulted downregulated in resistant chickens.…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review and meta-analysis of the virus shedding of avian influenza viruses [ 8 ] considered different explanatory variables for the viral shedding of AIVs in poultry species such as pathotype (HPAI/LPAI), shedding route, virus origin, inoculation route, age and chicken categories; it is reported that low viral shedding in chicken can be due to the avian host from which the virus originated. Moreover, some avian genes involved in resistance to clade 2.3.4.4b H5N8 HPAIV in commercial broilers (Ross 308 Broiler) and six local Spanish chicken breeds have recently been experimentally investigated [ 12 ] and PLAU, VCAM, TNFRSF1-1A and PGF gene expression, which are mainly involved in inflammation response, resulted downregulated in resistant chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TLR1A in the cecum tissue was significantly up-regulated on 7-days post infection with SE of White Leghorn Layer in our previous research [ 11 ]. The research that performed RNA-Seq from lung and spleen samples suggested that an early inactivation of important host genes could prevent an exaggerated immune response and/or viral replication, conferring resistance to HPAIV in chickens [ 12 ]. In addition, transcriptomic analysis revealed that more severe disease in line W chicken was associated with significant up-regulation of pathways involved in inflammation, cytoskeletal regulation by Rho GTPases, and Wnt signaling in the bursa, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, renal tubular epithelial ( RTE ) cells are a promising option for GAstV-2 proliferation and pathogenesis analysis. RNA sequencing ( RNA-seq ), a powerful approach that can provide precise measurements for transcriptome profiling, can reveal dynamic changes in host gene expression during pathogen infections, including various viral infections ( Ma et al, 2021 ; Pan et al, 2022 ; Perlas et al, 2021 ). Therefore, in the current study, we isolated goose primary RTE ( GRTE ) cells from goose embryos and investigated GAstV-2 growth characteristics in GRTE cells and GAstV-2–GRTE cell interactions through RNA-seq.…”
Section: Introductionmentioning
confidence: 99%